PENINGKATAN KONFLIK INTERKOMUNAL DI DARFUR SAAT OPERASI UNITED NATIONS INTEGRATED TRANSITION ASSISTANCE MISSION IN SUDAN (UNITAMS) PERIODE 2020-2022 - Thariq, Adha Altafi (2023)
In 2020, UNAMID had completed its mandate and withdrawn from Sudan periodically. The process of withdrawing UNAMID from Sudan is considered to have encountered several obstacles due to an increase in intercommunal conflict after the humanitarian conflict that occurred. This increase in intercommunal conflict was initiated due to the military coup that occurred in 2021 concerning the power struggle of the transitional government related to the people's uprising in 2019 which led to the overthrow of Omar Al-Bashir's government. Researchers will use the theory of peacebuilding which has a transformative nature related to the roles of UNITAMS and the Government of Sudan. In addition, researchers will also use the concept of conflict resolution to conduct an analysis of the increase in intercommunal conflicts that occur and what the possible results are. The researcher uses a research method that is descriptive analytical which is equipped with a qualitative approach and the method used to collect data is a literature study. The authors' findings are that the departure of peacekeeping missions from conflicted countries such as Sudan with conditions that have not been fully resolved can create new vulnerabilities that have the potential for other conflicts to arise. The launch of a special political assistance mission in Sudan such as UNITAMS is considered to be able to relieve the tension so that the country will be both politically and economically stable. The strengthening of political sector based on democracy can restore economic conditions so that sustainable peace can be achieved.